Fluoxetine versus Vitex agnus castus extract in the treatment of premenstrual dysphoric disorder - Atmaca, M; Kumru, S; Tezcan, E (Wiley, 2003)
Clinical trials have demonstrated that serotonin reuptake inhibitors (SRIs) and the extract of Vitex agnus castus are effective for the treatment of premenstrual dysphoric disorder (PMDD). However, to the best of our knowledge, there has been no study comparing the efficacy of the SRIs with Vitex agnus castus (AC) extract. Therefore, the aim of the present study was to compare the efficacy of fluoxetine, a selective serotonin reuptake inhibitor (SSRI), with that of the AC extract, a natural choice. After a period of 2 screening months to screen the patients for suitability, 41 patients with PMDD according to DSM-IV were recruited into the study. The patients were randomized to fluoxetine or AC for 2 months of single-blind, rater-blinded and prospective treatment period. The outcome measures included the Penn daily symptom report (DSR), the Hamilton depression rating scale (HAM-D), and the clinical global impression-severity of illness (CGI-SI) and -improvement (CGI-I) scales. At endpoint, using the clinical criterion for improvement, a similar percentage of patients responded to fluoxetine (68.4%, n = 13) and AC (57.9%, n = 11). There was no statistically significant difference between the groups with respect to the rate of responders. This preliminary study suggests that patients with PMDD respond well to treatment with both fluoxetine and AC. However, fluoxetine was more effective for psychological symptoms while the extract diminished the physical symptoms. Copyright (C) 2002 John Wiley Sons, Ltd.
Keywords: -premenstrual dysphoric disorder; fluoxetine; Vitex agnus castus; efficacy; SSRI